Design and testing of an experimental IPv4-to-IPv6 transition network / Mustaffa Samad - Samad, Mustaffa (Institute of Research, Development and Commercialisation (IRDC), 2006)
The Internet has been an integral part of the Information and Communication Technology (ICT) community in recent years. New internet users have been growing steadily over the years. This has lead to the depletion of new Internet Protocol (IP) addresses worldwide. To overcome this predicament, the new Internet Protocol version 6 (IPv6) had been introduced. The existing Internet Protocol version 4 (IPv4) is expected to be eventually replaced by this IPv6. The changeover from IPv4 to IPv6 is expected to be implemented progressively. During this transition period, these two protocols are expected to coexist for a number of years. IPv4-to-IPv6 transition tools have been designed to facilitate a smooth transition from IPv4 to IPv6. The two most basic IPv4-to-IPv6 transition tools available are the hybrid stack mechanism and tunneling. Tunneling is the encapsulation of IPv6 traffic within IPv4 packets so they can be sent over an IPv4 infrastructure. This project was initiated to set up an experimental IPv6 testbed, in order to study the performance as well as transition and migration issues of IPv6 networks under controlled conditions. This paper looks at how tunneling can be performed over existing internetwork infrastructure at Fakulti Kejuruteraan Elektrik (FKE), UiTM.